Gender dynamics of mathematical problem solving in 3D geometry: A case study of secondary school students - Deti Sri Rahayu Rahayu; Mardianto Mardianto; Gemi Susanti Susanti; Hodiyanto Hodiyanto (Universitas PGRI Pontianak, 2025)
This study aims to analyze students' mathematical problem-solving abilities in three-dimensional geometry using Polya's four stages: understanding the problem, devising a plan, carrying out the plan, and looking back. Data were collected through a written geometry task on pyramid solids and in-depth interviews with one male and one female student. The findings reveal that the male student successfully understood the problem, planned the solution, and executed calculations accurately, yet made a minor procedural error by omitting the square root symbol when applying the Pythagorean theorem. The female student experienced more complex conceptual and procedural errors, including confusing volume with surface area, misidentifying the altitude of the triangular face, and miscalculating its area. Interviews confirmed that these errors stemmed largely from inattention to the relationships between two- and three-dimensional concepts, despite an overall awareness of the distinctions. These results indicate that mastery of spatial geometry requires both strong conceptual understanding and procedural accuracy, supported by multi-dimensional representations to ensure effective problem solving. The study recommends incorporating multi-representational teaching, structured error analysis, and real-world contexts to reduce geometry misconceptions and enhance precision in mathematical problem-solving.